DEN GODA MARKNADSFÖRINGEN - Nilsson Savén,Niklas; Ask,Josefine (2007)
The term “good marketing practice” in the 4 § 1 section Swedish marketing law (Marknadsföringslagen 1995:450) has a wide meaning. Besides 5-13 d §§ and 17 §, the term also covers other non legal rules. The essay intends to define the legal meaning of the term as well as examine how it is experienced of laymen in the area. According to 1 § Swedish Marketing law aims to protect business men and consumers from unjustified marketing. Thus, the law can not be applied on marketing that is sexually discriminating or discriminating according to ethnicity, religion or sexual behaviour. The consequence of this is that the business community has developed their own measures that examine whether a marketing measure is compatible with good business conduct. The ethical council against sexual discrimination (ERK) and Marknadsetiskarådet (MER) is two of the business communities developed measurement systems. The council base their statements on the International Chamber of Commerce (ICC) basic rules for publicity. The essay contains statements from both councils in order to present what should be included in the term of good marketing practice. The essay further contains a thorough study of the term based on the court of market practice in the area. In order to get broader perspectives of the meaning of the term good marketing practice the essay also consists of an empirical study of how laymen experiences of the term. Semistructured deep interviews have been conducted with a number of advertising agencies in order to get an opinion of how the term is complied within the everyday activity. The empirical survey performed has shown that the Advertising agencies claims to be self adjusting according to legal jurisdiction. Decisions are often made out of co-workers common sense based on experiences and their own moral values. Keywords: Good marketing practice, marketing, advertising agency, norm rule, ethics
Keywords: Marknadsföring; Etik; Reklambyrå; god marknadsföringssed; normregler; Juridical science; Rättsvetenskap, juridik